Survival-Weighted Health Profiles in Patients Treated for Advanced Oral Cavity Squamous Cell Carcinoma - Tsai, Yao-Te; Chen, Wen-Cheng; Hsu, Cheng-Ming; Tsai, Ming-Shao; Chang, Geng-He; Lee, Yi-Chan; Huang, Ethan I.; Fang, Chiung-Cheng; Lai, Chia-Hsuan (Frontiers in Oncology, 2021)
Objectives: For patients with oral cavity squamous cell carcinoma (OSCC), particularly for those with advanced disease, quality of life (QoL) is a key outcome measure. Therefore, we estimated survival-weighted psychometric scores (SWPS), life expectancy (LE), and quality-adjusted LE (QALE) in patients with advanced OSCC. Methods and materials: For estimation of survival function, we enrolled 2313 patients with advanced OSCC diagnosed between January 1, 2007, and December 31, 2013. The patients were followed until death or December 31, 2014. To acquire the QoL data, data from 194 patients were collected by employing the Taiwan Chinese versions of the Quality of Life Questionnaire Core 30 and Quality of Life Questionnaire Head and Neck 35 developed by the European Organisation for Research and Treatment of Cancer and the EQ-5D-3L between October 1, 2013, and December 31, 2017. The LE of the patients with OSCC were estimated through linear extrapolation of a logit-transformed curve. SWPS and QALE were determined by integrating the LE and corresponding QoL outcomes. Results: For the patients with advanced OSCC, the estimated LE and QALE were 8.7 years and 7.7 quality-adjusted life years (QALYs), respectively. The loss of LE and QALE was 19.0 years and 20.0 QALYs, respectively. The estimated lifetime impairments of swallowing, speech, cognitive functioning, physical functioning, social functioning, and emotional functioning were 8.3, 6.5, 6.5, 6.1, 5.7, and 5.4 years, respectively. The estimated lifetime problems regarding mouth opening, teeth, social eating, and social contact were 6.6, 6.1, 7.5, and 6.1 years, respectively. The duration of feeding tube dependency was estimated to be 1.6 years. Conclusions: Patients with advanced OSCC had an estimated LE of 8.7 years and QALE of 7.7 QALYs. SWPS provided useful information regarding how advanced OSCC affects the subjective assessment of QoL. Our study results may serve as a reference for the allocation of cancer treatment resources.